Effective Communication Strategies in Improving the Perfomance of Islamic Education Organizations at Al-Ghozali Integrated Islamic Junior High School Jember - Fitriani, Kharisma; Ittaqi Tafuzi, Qonita; Rahmah, Nailatur; Nafa’ani, Nihlah; Aifah Rizqiyah, Novi; Mu’alimin, Mu’alimin (JUPE : Jurnal Pendidikan Mandala, 2024)
Islamic education is an essential element in community development that requires effective communication strategies to enhance organizational performance. This research employs a qualitative research approach with a literature review method to analyze effective communication strategies in the context of Islamic education. The discussion covers the definition of communication, factors influencing communication, indicators of effective communication, strategies that can be applied in the context of Islamic education, as well as barriers and challenges that may arise in the communication process. Additionally, this study explores the relationship between effective communication and the improvement of organizational performance in Islamic education. The findings of this research are expected to make a significant contribution to the development of more effective communication strategies for enhancing the performance of Islamic education organizations. Furthermore, this study is also expected to provide a deeper understanding of the importance of communication in the context of Islamic education.